Medicare Part D's Effects on Drug Utilization and Out‐of‐Pocket Costs: A Systematic Review - Park, Young Joo (Health Serv Res, 2016)
OBJECTIVE: To update a past systematic review on whether Medicare Part D changed drug utilization and out‐of‐pocket (OOP) costs overall and within subpopulations, and to identify evidence gaps. DATA SOURCES/STUDY SETTING: Published and gray literature from 2010 to 2015 meeting prespecified screening criteria, including having a comparison group, and utilization or OOP cost outcomes. STUDY DESIGN: We conducted a systematic literature review with a quality assessment. DATA COLLECTION/EXTRACTION METHODS: For each study, we extracted information on study design, data sources, analytic methods, outcomes, and limitations. Because outcome measures vary across studies, we did a qualitative synthesis rather than meta‐analysis. PRINCIPAL FINDINGS: Sixty‐five studies met screening criteria. Overall, Medicare Part D enrollees have increased drug utilization and decreased OOP costs, but coverage gaps limit the program's impact. Beneficiaries whose insurance becomes more generous after enrollment had disproportionately increased drug utilization and decreased OOP costs. Outcomes among dual‐eligibles were mixed. CONCLUSIONS: There is strong evidence on how Medicare Part D and the donut hole coverage gap affect utilization and OOP costs, but weak evidence on how effects vary among dual‐eligibles or across diseases. Findings suggest that the Affordable Care Act's provisions to expand coverage and reduce the donut hole should improve patient outcomes.